Development of methods for recovering uranium from sludge-like uranium generated in decontamination of metal wastes. Issue 3 (4th March 2017) - Ohashi, Yusuke; Tanaka, Yoshio; Tsunashima, Yasumichi; Ikeda, Yasuhisa
ABSTRACT: Sludge-like uranium wastes (SUWs) have been generated with neutralization of acidic aqueous solutions used for decontamination of metal wastes containing a large amount of iron. We have examined the method for recovering uranium from such SUWs using N -cyclohexyl-2-pyrrolidone (NCP) as a precipitate. As a result, it was found that precipitation ratios (PRs) of uranium in the solutions prepared by dissolving SUWs in HNO3 increase with increasing an amount of added NCP and are 97.7% at [NCP]/[U(VI)] = 20, and that the PRs of iron, aluminum, fluorine, and sulfate species are less than 1% at [NCP]/[U(VI)] = 3–20. This indicates that uranium species are precipitated selectively. The content ratios of U, Fe, Ca, F, and S in the materials after calcining precipitates obtained at [NCP]/[U(VI)] = 20 were 73, 2.2 × 10 −1, <3 × 10 −3, 2.3 × 10 −2, and 2.2 × 10 −2 wt%, respectively. These values are in accordance with the conditions of uranium ore concentrate defined by ConverDyn Corp and ASTM C967. From these results, it is expected that highly purified uranium can be efficiently recovered from SUWs by using NCP as the precipitant.